Mesenchymal Stem Cell Conditioned Medium as Good as Methyl Prednisolone in Decreasing Levels of Interleukin 10 and The Degree of Pulmonary Vasculitis in Lupus Mice (Bangladesh Journal of Medical Science, 2021)
Background: Systemic lupus erythematosus is a chronic autoimmune disease that affects target organs. mesenchymal stem cell conditioned medium has immunosuppressive, anti-inflammatory, and immunoregulatory properties in lupus. Methyl prednisolone is a standard drug for lupus with immunosuppressive and anti-inflammatory properties. This study aims to compare the therapeutic effect of mesenchymal stem cell conditioned medium administration compared to methyl prednisolone on interleukin 10 levels and the degree of pulmonary vasculitis of lupus mice.Methods: The subjects were 24 female mice of Mus musculus Balb/C strain, which were categorized into 4 groups of 8 mice, i.e. the control group receiving 0.5 cc of 0.9% NaCl injection and placebo, the lupus group receiving 0.5 cc of pristane injection and placebo, and the treatment mesenchymal stem cell conditioned medium group receiving 0.5 cc pristane injection and mesenchymal stem cell conditioned medium 0,5 cc, and methylprednisolone group receiving 0,5 cc pristiane injection and methylprednisolone p.o 1,5 mg/kgbodyweight. After 24 days the mice were terminated and kidney and blood samples were taken. Statistical analysis was performed using ANOVA test followed by independent T-test. The p value was considered significant when the p < 0.05.Results: The study showed that there was no difference on the levels of interleukin level10 among mesenchymal stem cell conditioned medium goup and methyl prednisolone group (CM = 5,94 ± 2,49 pg/mL, mp = 5,86+1,73 pg/mL; p = 1) and the degree of pulmonary vasculitis (CM= 1,94 ± 0,25, MP=1,89+ 0,11 pg/ml; p = 0.667). Mesenchymal stem cell conditioned medium as good as methyl prednisolone in decreasing levels of interleukin 10 and the degree of pulmonary vasculitis in lupus mice.Conclusion: Mesenchymal stem cell conditioned medium as good as methyl prednisolone in decreasing levels of interleukin 10 and the degree of pulmonary vasculitis in lupus miceBangladesh Journal of Medical Science Vol.20(2) 2021 p.426-430